THE ROLE OF MATHEMATICS IN MODERN ECONOMIC SCIENCES - V. M. Goncharenko; I. Ye. Denezhkina; V. Yu. Popov; A. B. Shapoval (Финансы: теория и практика, 2017)
Among a variety of innovative processes occurring in Russia in recent years, one of the most important is education reform. It is expected that upon the completion of the reform, Russian education system would meet the international standards of education and training. The fact that the role of mathematics in modern economics is increasing should be reflected in the educational process and the standards which are currently being developed by the Financial University. The paper suggests approaches to eliminate the existing discrepancy: with similar educational content in Russian and foreign universities, there is a deep gap in the study and application of quantitative methods. This gap leads to a decrease in the competitiveness of Russian graduates.